Spectroscopic (IR, UV, NMR) characterization of 4, 8 -di methyl 2, 6 -di phenyl 1, 5 -di hydro S-Indacene and study of effect of substituents in its electronic properties (Bulletin of Pure and Applied Sciences-Chemistry, 2019)
In the present study, quantum computational  methods such as semi empirical, Hartree fock  and density functional theory (DFT) are used for  the analysis of molecular structure of 4, 8-di  methyl, 2, 6 - di phenyl, 1, 5 - di hydro S Indacene. Vibrational analysis was carried out  using DFT method with the basis set B3LYP/6– 31G (d, p) and the infrared and Raman spectra of  title compound were reported. Frequency  assignments of the vibration spectra were carried  out with potential energy distribution (PED).  Optimization of the title compound were  calculated by the methods AM1, PM6, HF/6-31G  and B3LYP/6-31G (d, p) basis set in gas phase.  Furthermore, effect of substituents of the title  molecule on its electronic properties such as  HOMO-LUMO energy gap, absorption maxima  and oscillator strengths in UV-Vis spectrum,  NBO analysis, TDOS, Fukui function and the  local softness and eletrophilicity indices were  calculated. The thermodynamic properties have  also been calculated and predicted the  relationship of these properties with temperature.
Keywords: Semi empirical methods; S-indacene; Fukui function; Electrophilicity indices; B3YLP